Implementation of the school literacy movement during the covid-19 pandemic - Atikah Mumpuni; Prasetyo Yuli Kurniawan; Rizki Umi Nurbaeti; Annisa Nurul Fadillah; Meri Yuliyanti; Nova Indriyani (Universitas PGRI Madiun, 2021)
The implementation of the school literacy movement, especially in elementary schools, has many obstacles. Moreover, during the Covid-19 pandemic, the problem of implementing the school literacy movement became increasingly complex. This research is a qualitative research, which is carried out in elementary schools in Banjarharjo District. The data collection instruments consisted of interviews, questionnaire sheets, and observation sheets. The results showed 1) the pattern of literacy movements during the Covid-19 pandemic was adjusted to the level of developmental age of students and the situation and conditions and stages of the literacy movement carried out online; 2) The driving factors for the implementation of the school literacy movement during the Covid-19 pandemic include the availability of good facilities and cooperation with parents. Meanwhile, The inhibiting factors for the school literacy movement are the lack of supporting facilities and the lack of teachers to directly control the development of students' literacy. The school literacy movement during the Covid-19 pandemic should be supported by digital-based reading materials and parental understanding regarding the implementation of the school literacy movement during the Covid-19 pandemic.